2012
DOI: 10.1159/000334930
|View full text |Cite
|
Sign up to set email alerts
|

Tachyphylaxis to the Sumatriptan-Induced Contractile Effect in the Human Uterine Artery but Not in Human Cerebral Blood Vessels: Pharmacological Demonstration of the 5-HT<sub>1B</sub> Receptor Functionality Loss

Abstract: The in vitro contractile response of the human uterine artery to sumatriptan was compared to that of human cerebral blood vessels. Artery rings were prepared for isometric contraction. Tachyphylaxis to the triptan-induced vascular contraction was observed in the uterine artery, but not in basilar and middle cerebral arteries. To evaluate 5-HT1 receptor subtypes functionality, concentration-response curves to sumatriptan were performed at 0 and 24 h after uterine artery isolation. Both 10 µmol/l cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…These results may suggest that canine uterine tissue might exhibit desensitisation of 5-HT receptors as a result of the presence of oestrogen pre-neutering causing a prolonged exposure to 5-HT [13]. One human study evaluating uterine artery contractility to sumatriptan, a 5-HT 1 receptor agonist [28], showed that tachyphylaxis occurred in uterine arteries and also showed that this does not occur with cerebral arteries [28].…”
Section: Plos Onementioning
confidence: 99%
“…These results may suggest that canine uterine tissue might exhibit desensitisation of 5-HT receptors as a result of the presence of oestrogen pre-neutering causing a prolonged exposure to 5-HT [13]. One human study evaluating uterine artery contractility to sumatriptan, a 5-HT 1 receptor agonist [28], showed that tachyphylaxis occurred in uterine arteries and also showed that this does not occur with cerebral arteries [28].…”
Section: Plos Onementioning
confidence: 99%